2018
DOI: 10.1093/mnras/sty520
|View full text |Cite
|
Sign up to set email alerts
|

X-ray study of a sample of FR0 radio galaxies: unveiling the nature of the central engine

Abstract: FR0s are compact radio sources that represent the bulk of the Radio-Loud (RL) AGN population, but they are still poorly understood. Pilot studies on these sources have been already performed at radio and optical wavelengths: here we present the first Xray study of a sample of 19 FR0 radio galaxies selected from the SDSS/NVSS/FIRST sample of Best & Heckman (2012), with redshift ≤ 0.15, radio size ≤ 10 kpc and optically classified as low-excitation galaxies (LEG). The X-ray spectra are modeled with a power-law c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 91 publications
(124 reference statements)
12
49
0
Order By: Relevance
“…We therefore agree with Torresi et al (2018), who concluded that the AGN of NGC 6338 is X-ray faint, and place stronger limits on its luminosity. It should be noted that the high central density found in NGC 6338 (see Section 3.2) is therefore very unlikely to be biased by AGN emission.…”
Section: Active Nucleisupporting
confidence: 92%
“…We therefore agree with Torresi et al (2018), who concluded that the AGN of NGC 6338 is X-ray faint, and place stronger limits on its luminosity. It should be noted that the high central density found in NGC 6338 (see Section 3.2) is therefore very unlikely to be biased by AGN emission.…”
Section: Active Nucleisupporting
confidence: 92%
“…We use two FR 0s as reference ( Figure 4): while one is Tol 1326 − 379, detected by Fermi, the other source is a nearby (z=0.04) FR 0 radio galaxy, J160426.51+17. It shows a flat X-ray spectral index (Γ X = 1.1 ± 0.3) and X-ray luminosity similar to Tol 1326 − 379 (see [30]) that make it a potential candidate for a γ-ray detection. As an exercise, we adjusted the model adopted for Tol 1326 − 379 to reproduce the SED of J160426.51+17 (Figure 4b): the output in the GeV window could be just at the Fermi detection limit.…”
Section: Perspectives With Upcoming Mev-tev Observatoriesmentioning
confidence: 87%
“…Another proof of the misaligned nature of FR 0s comes from the distribution of the ratio between [O III] and X-ray luminosities (R [OI I I]/X ). While FR 0s and FR Is show similar values of R [OI I I]/X ∼ −1.7 (e.g., [38,44]), low-luminosity blazars have R [OI I I]/X ∼ −3.3 (e.g., [30,45]) as expected if the X-ray emission is beamed. Are they small fading FR Is?…”
Section: The Uniqueness Of the Fr 0 Classmentioning
confidence: 91%
See 1 more Smart Citation
“…We also do not discuss here the more evolved radio galaxies, classified morphologically as Medium Symmetric Objects (MSOs), and/or spectrally as Compact Steep Spectrum (CSS) sources (see Kunert-Bajraszewska et al 2014). Finally, we do not include the Fanaroff-Riley type 0 (FR0) radio galaxies (Glowacki et al 2017;Torresi et al 2018 WISE is an all sky survey mission covering the entirety of the northern and southern sky. The telescope obtains measurements in four bands (W1-W4) centered at 3.4, 4.6, 12, and 22 µm respectively.…”
Section: Introductionmentioning
confidence: 99%